WebMap: Web Map Development by a QGIS Complement - Amorim, Fabricio Rosa (2021)
This work aims to describe the construction process and the validation of a plugin / tool in Geographic Information Systems (GIS), used for the development of Web maps. For this, the WebMapa plugin, still under development, allows adding cartographic elements to Web pages, making them interactive and adaptable. The GIS was built as a complement (WebMapa plugin) to the QGIS software, using a python programming language. The pluginwas developed as a search engine that allows users to choose information and map elements, as well as symbolize them. The options made possible the choices of the following map elements: cartographic base (eg: OpenStreetMap, Google Maps); compass; scale; user's location on the map; screen editing; route calculation between starting and ending points. The result of the processing of the WebMapa plugin was built as a website available in the .html output format (HTML - Hypertext Markup Language). In this way, the system becomes multiplatform since it can be accessed as a Website in any type of Web browser, regardless of the operating system.